汉麻仁多肽对高尿酸血症斑马鱼的降尿酸 作用及其氨基酸序列分析Effect of hemp kernel polypeptide on reducing uric acid in zebrafish with hyperuricemia and analysis of its amino acid sequence - 魏连会，董艳，石杰，李国巍，张正海，姬妍茹，杨庆丽，潘静WEI Lianhui, DONG Yan, SHI Jie, LI Guowei, ZHANG Zhenghai, JI Yanru, YANG Qingli, PAN Jing (Zhongguo youzhi, 2025)
为促进汉麻仁多肽在功能食品及特医食品领域的应用，利用斑马鱼模型研究汉麻仁多肽的降尿酸作用及可能的机制，分析降尿酸活性肽组分的氨基酸序列。采用10 mmol/L尿酸酶活性抑制剂氧嗪酸钾和50 μmol/L尿酸合成前体黄嘌呤钠盐饲喂斑马鱼20 h，建立斑马鱼高尿酸血症模型。以别嘌呤醇为阳性对照，以不同质量浓度的汉麻仁多肽饲喂斑马鱼，测定斑马鱼的尿酸荧光强度、次黄嘌呤鸟嘌呤磷酸核糖基转移酶（HPRT1）和有机阴离子转运蛋白（OAT1）基因的mRNA表达，利用液相色谱-串联质谱技术对降尿酸活性肽组分氨基酸序列进行分析。结果表明：汉麻仁多肽能够通过上调HPRT1和OAT1基因表达，有效降低高尿酸斑马鱼的尿酸水平；汉麻仁多肽活性组分中丰度较高的8个峰对应的肽段分子质量分别为499.23、578.24、628.27、653.29、715.31、918.43、982.41、1 128.49 Da，其氨基酸序列分别为PGTPE、MPDDV、TTSYTG、TPHWN、NNGDSPL、DDFNPRR、NPHDEFQP、YHSYLCKTD。综上，汉麻仁多肽可作为功能性成分用于降尿酸相关功能食品和保健品的开发。In order to promote the application of hemp kernel polypeptide in functional foods and specialty medical foods, the uric acid-lowering effect and its possible mechanisms of hemp kernel polypeptide in zebrafish model were investigated, and the amino acid sequences of polypeptide components with uric acid-lowering activity were analyzed. The zebrafish hyperuricemia model was established by feeding zebrafish with an uricase inhibitor potassium oxonate at 10 mmol/L and uric acid synthesis precursor xanthine sodium salt at 50 μmol/L for 20 h. Hemp kernel polypeptide with different mass concentrations administered to the zebrafish, with allopurinol as a positive control. The fluorescence intensity of uric acid, and mRNA expression of hypoxanthine guanine-phosphoribosyltransferase(HPRT1) and organic anion transporter(OAT1) gene in zebrafish were measured. The amino acid sequences of the active polypeptides were analyzed by liquid chromatography-mass spectrometry. The results showed that hemp kernel polypeptide effectively reduced uric acid level of zebrafish through up-regulating HPRT1 and OAT1 gene expression. The molecular weight of eight polypeptides with high abundance in hemp kernel polypeptide were 499.23, 578.24, 628.27, 653.29, 715.31, 918.43, 982.41, 1 128.49 Da, and their amino acid sequences were PGTPE, MPDDV, TTSYTG, TPHWN, NNGDSPL, DDFNPRR, NPHDEFQP, YHSYLCKTD, respectively. In conclusion, the hemp kernel polypeptide can be used as functional components in the development of functional food and health care products related to lowering uric acid.